Indirect hemagglutination test for detection of antibodies to cytomegalovirus in blood collected on blotting paper (author's transl) - Cabau, N; Duros, C; Ravisé, N; Coulon, M; Boué, A (Pathologie biologie (Paris), 1976)
Indirect hemagglutination test for detection of antibodies to cytomegalovirus is highly sensitive and reproducible, if employed in well-defined conditions. Standardization of the various factors involved is necessary as well as their reciprocal equilibrium : sheep erythrocytes, antigen, dilution of tanin, buffers quality. The hemagglutination test can be performed on small volumes such as blood collection on blotting paper (PKU). Antibody titers were compared in the serum and the blood so collected in 104 subjects : the results were very similar and no "false negative" were found in any case. This way of collecting blood and hemagglutination are technical improvements in epidemiologic studies of cytomegalovirus infection. It can be hoped they will be adapted to other group herpes infections.